Impact of preoperative echocardiography on surgical delays and outcomes among adults with hip fracture. (1st February 2021) - Chang, Justin S.; Ravi, Bheeshma; Jenkinson, Richard J.; Paterson, J. Michael; Huang, Anjie; Pincus, Daniel
Abstract : Aims: Echocardiography is commonly used in hip fracture patients to evaluate perioperative cardiac risk. However, echocardiography that delays surgical repair may be harmful. The objective of this study was to compare surgical wait times, mortality, length of stay (LOS), and healthcare costs for similar hip fracture patients evaluated with and without preoperative echocardiograms. Methods: A population-based, matched cohort study of all hip fracture patients (aged over 45 years) in Ontario, Canada between 2009 and 2014 was conducted. The primary exposure was preoperative echocardiography (occurring between hospital admission and surgery). Mortality rates, surgical wait times, postoperative LOS, and medical costs (expressed as 2013 CAN) up to one year postoperatively were assessed after propensity-score matching. Results: A total of 2, 354 of 42, 230 (5.6%) eligible hip fracture patients received a preoperative echocardiogram during the study period. Echocardiography ordering practices varied among hospitals, ranging from 0% to 23.0% of hip fracture patients at different hospital sites. After successfully matching 2, 298 (97.6%) patients, echocardiography was associated with significantly increased risks of mortality at 90 days (20.1% vs 16.8%; p = 0.004) and one year (32.9% vs 27.8%; p < 0.001), but not at 30 days (11.4% vs 9.8%; p = 0.084). Patients with echocardiography also had a mean increased delay from presentation to surgery (68.80 hours (SD 44.23) vs 39.69 hours (SD 27.09); p < 0.001), total LOS (19.49 days (SD 25.39) vs 15.94 days (SD 22.48); p < 0.001), and total healthcare costs at one year (51, 714.69 (SD 54, 675.28) vs 41, 861.47 (SD 50, 854.12); p < 0.001). Conclusion: Preoperative echocardiography for hip fracture patients is associated with increased postoperative mortality at 90 days and one year but not at 30 days. Preoperative echocardiography is also associated with increased surgical delay, postoperative LOS, and total healthcare costs at one year. Echocardiography should be considered an urgent test when ordered to prevent additional surgical delay. Cite this article: Bone Joint J 2021;103-B(2):271–278.